The Relationship Between Basic Household Sanitation And Diarrheal Diseases In Samalanga Subdistrict Bireuen Regency 2024 - Nasrulah, Nasrullah; Junaidi, Junaidi; Syahrizal, Syahrizal; Kartini, Kartini (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2024)
Diarrhea, if not treated promptly, can lead to dehydration in children. Dehydration can range from mild to moderate to severe symptoms. Treatment includes administering oral rehydration salts (ORS) and immediately seeking hospital care. Substandard household environmental conditions are evident from the high incidence of diarrhea, with 30 cases reported in 2023. This study aims to examine the relationship between basic household sanitation and diarrheal diseases in Samalanga Subdistrict, Bireuen Regency, in 2024. This research is descriptive-analytical and employs a cross-sectional design. The population consists of 27,907 households, with a proportional sampling technique applied to select 100 respondents. The results indicate significant effects of clean water source sanitation (P-value = 0.001), SPAL sanitation (wastewater drainage systems) (P-value = 0.003), waste disposal sanitation (P-value = 0.010), and toilet sanitation (P-value = 0.001) on diarrheal diseases in Samalanga Subdistrict, Bireuen Regency, in 2024. The study concludes that the factors of clean water source sanitation, waste disposal facilities, SPAL sanitation, and toilet sanitation influence the incidence of diarrhea in Samalanga Subdistrict, Bireuen Regency, in 2024. It is recommended that local health centers (Puskesmas) enhance health education on diarrhea and Clean and Healthy Living Behavior (PHBS), particularly in preventing diarrhea